A Public instrument in the Court of Justice of Aragon - Urzainqui Biel, Carlos (Revista de derecho aragonés, 2023)
In this article, we analyze a document called «Public instrument before the Court of Justice of Aragon» about a confrontation between the Aragonese towns of Villanueva de Gállego and Zuera regarding rights and enjoyment of water in an irrigation ditch and based on a recognition granted by the Aragonese monarch Alfonso II in the year 1312. This document constitutes one of the few interdicts presented before said Justice of Aragon on customary regional issues that are preserved.